The potential role of lactulose pharmacotherapy in the treatment and prevention of diabetes - Chu, Natural; Ling, James; Jie, He; Leung, Kathy; Poon, Emily (Frontiers in Endocrinology, 2022)
The non-absorbable disaccharide lactulose is mostly used in the treatment of various gastrointestinal disorders such as chronic constipation and hepatic encephalopathy. The mechanism of action of lactulose remains unclear, but it elicits more than osmotic laxative effects. As a prebiotic, lactulose may act as a bifidogenic factor with positive effects in preventing and controlling diabetes. In this review, we summarized the current evidence for the effect of lactulose on gut metabolism and type 2 diabetes (T2D) prevention. Similar to acarbose, lactulose can also increase the abundance of short-chain fatty acids (SCFAs)-producing bacteria Lactobacillus and Bifidobacterium, as well as suppressing the potentially pathogenic bacteria Escherichia coli. These bacterial activities have anti-inflammatory effects, nourishing the gut epithelial cells and providing a protective barrier from microorganism infection. The activation of peptide tyrosine tyrosine (PYY), and glucagon-like peptide 1 (GLP1) can influence secondary bile acids and reduce lipopolysaccharide (LPS) endotoxins. A low dose of lactulose with food delayed gastric emptying and increased the whole gut transit times, attenuating the hyperglycaemic response without adverse gastrointestinal events. These findings suggest lactulose may have a role as a pharmacotherapeutic agent in the management and prevention of type 2 diabetes via actions on the gut microbiota.